Response of yearling steers to burning and fertilizing pasture and intensive early season stocking (bluestem pastures) - Harbers, L.H.; Schalles, R.R.; Smith, E.F.; Owensby, Clenton E.; Boggs, Don (Kansas State University. Agricultural Experiment Station, 2011)
Nine pastures totaling 492 acres were summer grazed by yearling Hereford, Hereford-Angus cross, and Angus steers distributed equally by breed. Five pastures were burned April 22, 1975; four were not burned. Burned and nonburned pastures had 0, 40, or 80 lbs. of nitrogen per acre applied aerially April 29, 1975. Stocking rates were determined with herbage production data from experimental plots under similar treatments. Under equal fertilization and stocking ratios, burned and fertilized pastures produced as much or more average daily gain and more gain per acre than nonburned pastures. Fertilizing and heavier stocking tended to reduce average daily gains but increased gains per acre. Steers on the early season, intensely-stocked pasture gained the most per day (1.78 lbs.) and produced the highest gain per acre (70 lbs.).
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Yearling steers; Fertilizer; Bluestem pasture